Factors influencing customer loyalty in the South African mobile phone market. - Nkhumeleni, Mpho (My University, 2014)
ABSTRACT The competition in mobile phone market in South Africa has become fierce and all mobile operators have realised that they need to protect their existing customer base. Industry revenue grew at an average of 40% in the beginning of the last decade compared to 4% at the end of the decade. Customer churn to other technologies such as Internet Protocol Systems threatens the existence of mobile phone service providers. These technologies offer voice and/or video communication markets (e.g. Skype) using fixed line phones. It is therefore important to understand factors that influence customer loyalty in the South African mobile phone market to eliminate the churn. Mobile phone operators’ tend to focus on customer lock-in strategies such as bundling of services and devices, fixed term contracts, and offering of handsets locked to a particular network (Pynnonen, 2008) rather than customer loyalty. The author is not aware of any academic study that focused on customer loyalty in the South African mobile phone market. Given the nature of the research problem and the purpose of the research, the most appropriate research method was survey questionnaires that were administered to a stratified random sample of 107 mobile phone subscribers. The questionnaire contained various questions and statements that represented constructs suggested by the literature review. A five-point Likert scale rating and open-ended questionnaire was used in collecting responses. The main findings of this study indicated that the South African mobile phone customers are influenced by seven (7) factors. Factors showed valid internal reliability with the construct identified in the literature survey. The resulting model used the F statistic that significantly suggested an overall relationship in the data, i.e. together these factors have a strong predictive value in Customer Loyalty. The study concluded that customer satisfaction and trust have a positive effect on customer loyalty. Corporate image and service quality have a weak influence on customer loyalty and switching cost demonstrated no positive effect on customer loyalty. South Africans appear to be more committed to their chosen network provider and their chosen brand of handset.There is not enough service and product differentiation in the mobile phone market in South Africa. Better handset deals at the time of acquiring the mobile phone seems to be what makes customer choose the service provider. Customers would rather keep to their current service provider as there are no compelling reasons to switch service provider. In the long term, the mobile phone service providers should look beyond low rates when it comes to keeping good customers and encouraging loyalty. They should focus on the factors that influence customer loyalty as themes of Customer Relationship Management (CRM). Striving to improve CRM performance will help to attain a higher level of customer loyalty.
MBA 2012
Keywords: Cell phone services industry, Mobile communication systems, Consumer behavior.